Titanium and vanadium based bimetallic prussian blue analogue as a cathode material for sodium ion batteries - Omama, Javed (2023)
The growing need for alternative and renewable energy sources has led to a higher need for robust and readily available energy storage solutions. So far, the sodium ion battery (SIB) has demonstrated superior performance compared to lithium-ion batteries. However, it still faces challenges related to the cathode materials, such as limited energy density, structural integrity issues, and cycle stability concerns. As a result of these challenges, the process of scaling up and commercialization of sodium ion batteries is currently facing difficulties. The designing of cathode material is a straightforward approach to enhance the overall efficiency of the sodium ion battery. The main objective of this research is to investigate how varying concentrations of dopants in the cathode sample impact its electrochemical performance, specifically in terms of its specific capacity and stability during the charge-discharge cycle. For this purpose, this study aimed to prepare various samples of sodium titanium vanadium hexacyanoferrate with varying ratios of titanium and vanadium with ratios of 1:1, 3:7, 4:6, 6:4, and 7:3 were produced. These samples were first characterized by XRD, FESEM-EDX, BET, and FTIR to analyse the structural and compositional details of all the prepared cathode materials. The FESEM-EDX showed cubic shaped consistent all the samples which matches best with its XRD as well in which clear peaks of PBA and sodium were observed at 17o and 31o respectively. The functionality of the materials was confirmed by the identification bands in FTIR at 1634 cm-1 represents the strong C=C stretching bond and the bond at 961 cm-1 represents the strong C=C bending bond. The broad peak at 3500 cm-1 represents the presence of strong O-H bond. Average pore size in the range of 40-70 nm was achieved on BET testing. An overall comparison of all the materials shows that Ti:V 1:1 showed better morphology and diffraction pattern with good pore size. The electrochemical performance was analysed by cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) testing. The CV showed clear and promising redox peaks at 3.25 V which supports the redox behaviour of the prepared samples during charge-discharge cycles in SIB set-up. The same was further confirmed by GCD plots where charging and discharging curves are achieved in relevant potential window of 1.5-4.5 V for all the prepared and tested samples. The specific capacity was also calculated for all the scan rates. To evaluate the cyclic stability of the cathode material, the long-term charge discharge cycles were run for a span of 50 cycles. From all the analyses done, it can be concluded that the sample with ratio 1:1 giving the best overall performance compared to the others.